(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2022)
Cocoa is a product with great advantages, arising from domestic demand and increasing the export of chocolate products, however; the sensory evaluation of the color of cocoa liquor is still subjective to the human eye, and this can affect the marketing and its industry, therefore, research in Colombia is focused on finding materials that are of acceptable bean quality in domestic and international markets. The objective of this work was to evaluate the colorimetric and physicochemical characteristics of clones CCN51, FEAR5 and FEC2. The samples were grown and harvested at the hot water headquarters of SENA in the municipality of Playón Santander Colombia, and 18 cobs of each clone were transported to the microbiological analysis laboratory of the Center for Agricultural and Livestock Sector Services (Centro de Atención al Sector Agropecuario C. A.S.A. of SENA in the municipality of Piedecuesta, where they were disinfected and adapted for manual extraction of the pulp and the beginning of the fermentation and drying process.